Analyzing and considering inertial effects in powered lower limb prosthetic design - Beckerle, Philipp; Wojtusch, Janis; Seyfarth, Andre; Von Stryk, Oskar; Rinderknecht, Stephan (IEEE International Conference on Rehabilitation Robotics, 2015)
Powered lower limb prostheses are designed to restore the biomechanical functionality of missing parts of their users' bodies. However, they do not yet meet the versatility and efficiency of the biological counterpart. A crucial open issue is how the prosthetic system and its actuator should be designed to achieve an energy efficient operation. This paper proposes a novel methodology for the design and optimization of elastically actuated lower limb prostheses. In contrast to other studies, actuator inertia is considered in this paper. Further, the approach considers the inertial parameters of the prosthesis after initial design to revise the requirements and redesign the system. The design procedure is described and presented for the example of a powered prosthetic knee. In this, considering actuator inertia enables to find optimal stiffness values for walking that are not to be found with common methods and altered optimal values for other gait types. Further, the consideration of the inertial properties of the pre-designed prosthesis in a gait simulation lead to distinctly lower requirements for peak power. For walking those are decreased by about 10% while in running a reduction of over 30% is observed. Analyzing those results, the potential of considering actuator and prosthetic inertia in design and thus the benefits due to the presented method are pointed out.
CRIS-Team Scopus Importer:2021-09-24